Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.energyfuels.3c01097
|View full text |Cite
|
Sign up to set email alerts
|

MILD Combustion of Solid Fuels: Its Definition, Establishment, Characteristics, and Emissions

Abstract: Moderate or intense low-oxygen dilution (MILD) combustion has the advantages of high thermal efficiency and ultralow NO x emissions. This technology has attracted extensive attention from the combustion community since 1990 or so. The early development of MILD combustion technologies required highly preheating the combustion air externally, thus limiting the range of its industrial applications, especially for burning solid fuels. Later, this technical limitation was gradually overcome, particularly becoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…Ariemma et al indicated that the increased OH production due to CH 4 oxidation consumes NH 2 radicals, which inhibits the DeNO x process. To mitigate high NO x emissions from NH 3 /CH 4 combustion, various combustion technologies have been adopted, including gliding arc-assisted combustion, , rich-lean combustion, , pressurized combustion, and flameless combustion. , In many studies, a small percentage of NH 3 is adopted as the fuel-N source. , As the NH 3 proportion increases, the concentrations of OH, N, and HNO radicals are altered, thereby influencing NO x formation characteristics. Zhang et al and Filipe Ramos et al both noted that the NO x emissions reach the peak value when the volume fraction of NH 3 in the fuel ( V NH 3 ) equals 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Ariemma et al indicated that the increased OH production due to CH 4 oxidation consumes NH 2 radicals, which inhibits the DeNO x process. To mitigate high NO x emissions from NH 3 /CH 4 combustion, various combustion technologies have been adopted, including gliding arc-assisted combustion, , rich-lean combustion, , pressurized combustion, and flameless combustion. , In many studies, a small percentage of NH 3 is adopted as the fuel-N source. , As the NH 3 proportion increases, the concentrations of OH, N, and HNO radicals are altered, thereby influencing NO x formation characteristics. Zhang et al and Filipe Ramos et al both noted that the NO x emissions reach the peak value when the volume fraction of NH 3 in the fuel ( V NH 3 ) equals 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Oxy-coal combustion (OCC) technology has garnered wide attention with the push for carbon neutrality. However, OCC has several drawbacks, including ignition delay, incomplete combustion loss, and low combustion stability. , Moderate and intense low-oxygen dilution (MILD) combustion, which extensively dilutes the oxidizer and preheats the fuel through intensively internal flue gas recycle (FGR), leads to a lower peak temperature, more uniform temperature distribution, extended reaction zone, and reduced reaction rate. , This technology not only improves thermal efficiency but also inhibits NO x emissions. By integrating the MILD combustion with the OCC technology, the MILD-OCC technology effectively mitigates the deficiencies of conventional OCC technology. , …”
Section: Introductionmentioning
confidence: 99%